Molecular Engineering of Nonplanar Porphyrin and Carbon Nanotube Assemblies- a Linear and Nonlinear Spectroscopic and Modeling Study - GIORDANI, SILVIA; SENGE, MATHIAS; RICKARD, DAVID; BLAU, WERNER (My University, 2011)
The importance of molecular conformation to the nature and strength of noncovalent interactions existing between a series of increasingly nonplanar tetraphenylporphyrin (TPP) derivatives and carbon nanotubes was systematically investigated experimentally in solution using a range of linear and nonlinear optical techniques. Additional complementary molecular dynamics studies were found to support the experimental observations. Convincing evidence of binding between single walled nanotubes (SWNTs) and some of these porphyrins was discovered, and a nonplanar macrocycle conformation was found to increase the likelihood of noncovalent binding onto nanotubes. Nonlinear optical studies showed that the optical limiting behavior of the TPP derivatives deteriorated with increasing porphyrin nonplanarity, but that formation of nanotube composites dramatically improved the optical limiting properties of all molecules studied. It was also found that the significant photoluminescence quenching behavior reported in the literature for such porphyrin/SWNT composites is at least partly caused by photoluminescence and excitation self-absorption and is, therefore, an artifact of the system.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; single-walled nanotubes (SWNTs); Porphyrin